Education for alln; Baywatch; Mountain high - Lazaro, Cheche (The Probe team, 1994)
To upgrade the achievement of public school students, they should be given additional teachers, improve school facilities and furnitures is viewed on the first part. Second, to safeguard Puerto princessa's waters, agroup named "Baywatch" or "Bantay Dagat" was formed. Lastly, mountaineering pioneered by U. P. students becomes a popular sport.